STRATEGIES ET ENJEUX DES ELECTIONS DES REPRESENTANTS FACULTAIRES DE L’UNIVERSITE DE KISANGANI - LINGAMA, Zéphyrin MAPESA (IJRDO - Journal of Social Science and Humanities Research, 2021)
This article takes a critical look at the vote of student representatives at the University of Kisangani in the Democratic Republic of Congo, which is a complex phenomenon to apprehend. It is a reflection on the strategies and issues developed by the candidate representatives of the students to occupy the position. Starting from strategic and ecological analyzes, this article shows that the elections of representatives constitute a real political competition where the actors resort to the quest for political sponsorship, the mobilization of ethnic or provincial solidarity, to a few techniques of political marketing for conquest, the exercise and conservation of power in the student environment.